2015
DOI: 10.1016/j.jcin.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transradial Coronary Catheterization on Upper Limb Function

Abstract: Upper limb function was not affected when coronary catheterizations and interventions were performed through the radial artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…1 For many patients undergoing diagnostic or interventional procedures, the shorter postprocedural monitoring, early ambulation, and less discomfort make TRA an attractive alternative to the transfemoral approach. 2 prohibitive lesion complexity or distance from the access site remain potential barriers to TRA uptake, along with concerns regarding major vascular complications and stroke. Nonetheless, in a number of studies of patients presenting with acute coronary syndromes, the estimated rates of major vascular complications occurring with TRA (hand ischemia, compartment syndrome, major bleeding) remain strikingly low, ~1.7% of cases, with stroke rates varying from 0.1% to 0.4%.…”
Section: Introductionmentioning
confidence: 99%
“…1 For many patients undergoing diagnostic or interventional procedures, the shorter postprocedural monitoring, early ambulation, and less discomfort make TRA an attractive alternative to the transfemoral approach. 2 prohibitive lesion complexity or distance from the access site remain potential barriers to TRA uptake, along with concerns regarding major vascular complications and stroke. Nonetheless, in a number of studies of patients presenting with acute coronary syndromes, the estimated rates of major vascular complications occurring with TRA (hand ischemia, compartment syndrome, major bleeding) remain strikingly low, ~1.7% of cases, with stroke rates varying from 0.1% to 0.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the trans-radial approach (TR) is a valuable alternative to the TF approach and has been shown to reduce access-site bleeding and vascular complications [11,12] and is possibly associated with better clinical outcomes in patients undergoing angioplasty. [13,14] Early ambulation, lower patient discomfort, also makes TR an attractive alternative to the TF approach [15]. For such reasons, the TR approach is now used not only in routine coronary procedures, but also in complex percutaneous coronary interventions, chronic total occlusion interventions and peripheral interventions [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, these end points were secondary in our study, and recent reports confirmed the lack of impact of radial catheterization on the upper limb function. 23 Radial spasm definition was prespecified in the study protocol according to accepted intravascular ultrasound consensus. 24 Still, radial spasm was evaluated only in the acute phase and the evidence of an image resembling spasm long after cannulation might be related with vessel remodeling.…”
Section: Limitationsmentioning
confidence: 99%